Natural Ventilation in Old Buildings: recommendations for its improvement - Salehi, Atefeh (2017)
Tese de doutoramento em Sistemas Sustentáveis de Energia, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra